Navigating Controversy as a Complex Search Task - Dori-Hacohen, Shiri; Yom-Tov, Elad; Allan, James (Elsevier, 2015)
Seeking information on a controversial topic is often a complex task, for both the user and the search engine. There are multiple subtleties involved with information seeking on controversial topics. Here we discuss some of the challenges in addressing these complex tasks, describing the spectrum between cases where there is a clear right answer, through fact disputes and moral debates, and discuss cases where search queries have a measurable effect on the well-being of people. We brie y survey the current state of the art, and the many open questions remaining, including both technical challenges and the possible ethical implications for search engine algorithms.